PENGEMBANGAN SISTEM INVENTARIS BERBASIS QR CODE MENGGUNAKAN WEB SERVICE PADA BIDANG SARANA DAN PRASARANA STMIK STIKOM INDONESIA - Putra, I Nyoman Tri Anindia (Jurnal Nasional Pendidikan Teknik Informatika (JANAPATI), 2018)
Web service is one of the methods which is very useful in solving problems in various fields such as from government, education, economics, social, culture. Web services can be defined as methods in exchanging data that can be done without paying attention to where the database is embedded and made in any language. Web services are able to support interoperability, so that the web service is able to become a bridge between various existing systems. STMIK STIKOM INDONESIA is an institution that has used an information system in managing all activities of the academic community within the institution. One of them is the inventory information system, but when doing the overall inventory there was a problem in synchronizing data in the field with the system. It required a long process and took a long time. So that a QR code-based inventory system was developed to simplify and speed up the synchronization process using a web service. The results of the study proved to be able to facilitate and accelerate the performance of staff in synchronizing data in the field with data on the system.